Effects Of Rh-Wma Additive On The Rheological Properties Of Reclaimed Asphalt Binders And The Engineering Properties Of Recycled Mixtures - Gungat, Lillian @ Lilia (2017)
Reclaimed asphalt pavement (RAP) utilization is an option as a sustainable pavement due to its economic and environmental benefits. However, the use of high RAP content in pavement construction implicates high production temperature and hence increasing energy consumption and environmental problems during the asphalt mixture production. Higher asphalt mixture production and compaction temperatures are needed because the RAP binder is oxidized and stiffened. Asphalt mixtures with very high stiffness are more susceptible to fatigue failure. This explains the reason why RAP usage is limited particularly in areas with high amount of aggregates resources. Therefore, this research investigates the performance of a relatively new warm mix asphalt (WMA) additive named RH-WMA additive to reduce asphalt production temperatures. The optimum RH-WMA content was determined through asphalt binder rheological tests. A total of 3% RH-WMA additive by mass of asphalt binder, was incorporated into the recycled asphalt binder and mixture. The effects of RH-WMA additive on recycled asphalt binder and mixture were investigated via chemical properties, rheological properties and mixtures performance test, respectively. The test results showed that the incorporation of RH-WMA additive with asphalt binder decreased the viscosity at high temperature and improved fatigue resistance at intermediate temperature. Viscosity reduction was also observed when RH-WMA additive incorporated with recycled asphalt binder and hence indicated the potential to reduce the production temperature of the RAP mixture. The Fourier Transform Infrared (FTIR) test result showed the ability of RH-WMA additive to reduce the effects of aging. The reduced effects on aging is also shown in the rheological master curves at high frequency and/or low temperature. From the rheological master curves, the addition of RH-WMA additive increased the complex modulus and reduced the phase angle values compared to the control sample. This observation showed that the recycled asphalt binder incorporated with RH-WMA additive showed potential improvement in rutting resistance. The optimum binder content (OBC) results based on response surface method (RSM) and multi criteria optimization in recycled asphalt mixture with RH-WMA additive production indicated the significant effects of mixing temperature on the OBC. The performance of recycled asphalt mixtures were improved in terms of stiffness and resistance to rutting. However, the asphalt mixture’s ability to resist fatigue decreased considerably when stiffer RAP from locations R1 and R3 were incorporated in the virgin mixture. The incorporation of RH-WMA additive improved the mixture’s resistance to fatigue. The combined effects of moisture and aging also decreased the fatigue resistance of all mixture types in comparison with unconditioned specimen. In general, the addition of RH-WMA additive can potentially balance the adverse effects of RAP stiffness and hence maximize the benefits of RAP usage.